Language in Professional Psychology Training: Towards Just Justice - Dlamini, Sipho (PINS-Psychology in Society, 2022)
The dominance of white, middle-class, English- and Afrikaans-speaking people within professional psychology, both in training and practice, continues the marginalisation of Black lifeworlds. As part of Black lifeworlds, language in the training of psychologists remains an important, but under-engaged aspect of the effectiveness of psychologists to render services to the South African population. Using Lewis R. Gordon’s work on justice, and drawing on the question, what is the training of psychologists for? I argue for the centralisation of language in the training of psychologists – and subsequent practice – as one way to alleviate the marginalisation of Black lifeworlds in professional psychology. To make visible how marginality and exclusion are enacted within psychology, I focus on the contestations brought about through language in higher education. I expand on unjust justice and just injustice as two ways in which Black lifeworlds have been rendered perpetually marginal during colonialism, apartheid and in democratic South Africa. I end the paper by gesturing towards possibilities of just justice through the selection of candidates for training into professional psychology.